1997
DOI: 10.3109/13682829709017898
|View full text |Cite
|
Sign up to set email alerts
|

Concordance between teacher/therapist opinion and formal language assessment scores in children with language impairment

Abstract: Abstracts As part of a wider study, 242 children attending language units attached to mainstream schools were assessed on a number of formal language assessments. In addition, each child's teacher was asked to state whether, for each of four areas of language difficulty, the participant exhibited this impairment. The four areas were: articulation, phonology, syntax/morphology and semantic/pragmatic impairment. This report compares test results between children thought by their teacher or therapist to show each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 18 publications
2
26
0
2
Order By: Relevance
“…However, children who moved schools were more likely to be described as having 'expressive only' language problems (44/84, 52% versus 41/118, 35%; x 2 (2)=10·9; p=0·004). (Recall that those who moved were better on standardized articulation and expressive grammar tests -good concordance between test and teacher data is reported elsewhere, by Botting et al 1997).…”
Section: Parent Opinion and Demographic Factorssupporting
confidence: 60%
“…However, children who moved schools were more likely to be described as having 'expressive only' language problems (44/84, 52% versus 41/118, 35%; x 2 (2)=10·9; p=0·004). (Recall that those who moved were better on standardized articulation and expressive grammar tests -good concordance between test and teacher data is reported elsewhere, by Botting et al 1997).…”
Section: Parent Opinion and Demographic Factorssupporting
confidence: 60%
“…Other studies have also highlighted the usefulness of spontaneous speech measures for diagnosing children with SLI who come from Spanishspeaking families (Restropo, 1998) or African-American families (Craig & Washington, 2000). Botting, Conti-Ramsden, and Crutchley (1997) investigated the sensitivity of standardized psychometric tests to different types of language disorders in a sample of more than 240 children ages 6-8 years old. They found that although such tests were good at discriminating children with structural language impairments, none of the tests could identify children with semantic-pragmatic disorders.…”
Section: Nih-pa Author Manuscriptmentioning
confidence: 99%
“…The participants in the present study are a subgroup drawn from an extensive longitudina l study examining a variety of issues surrounding English children attending language units (Conti-Ramsden and Botting, 1999;Botting et al, 1997Botting et al, , 1998. The original study examined 242 children (186 boys, 56 girls) in school year 2 (mean age 7:0).…”
Section: Participantsmentioning
confidence: 99%